Impact of Vaginal Estrogen on the Urobiome in Postmenopausal Women With Recurrent Urinary Tract Infection. Issue 4 (April 2022) - Jung, Carrie E.; Estaki, Mehrbod; Chopyk, Jessica; Taylor, Bryn C.; Gonzalez, Antonio; McDonald, Daniel; Shin, Jenny; Ferrante, Kimberly; Wasenda, Erika; Lippmann, Quinn; Knight, Rob; Pride, David; et al.
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2022;28:20–26) Up to 50% of women will have at least 1 urinary tract infection (UTI) in their lifetime, and 2% to 5% will experience recurrent UTIs (rUTIs). Postmenopausal women are disproportionately affected by both UTI and rUTI.